Alcohol-substance use disorders in hiv infection - Bakım, Bahadır; Karamustafalıoğlu, K.Oğuz; Öğütcen, Özgür; Yumrukçal, Hüseyin (Journal of Dependence, 2006)
Objective: Substance and/or alcohol use disorder is commonly associated with unprotectedsexual relations among populations at particular risk for human immunodeficiency virus (HIV), contributing to risky sexual behavior among men who have sex with men, drug users, young adults, and men seeking mental health and prevention services. These individuals have risk taking behaviors due to substance and/or alcohol use disorder and comorbid psychiatric disorders. HIV-infected individuals’ quality of life and compliance of pharmacotherapy improve with the treatment of comorbid psychiatric disorders. In this study, we discussed the important features related to the diagnosis, course and the treatment in the presence of substance and/or alcohol use disorder and other comorbid psychiatric disorders.Method: We searched PubMed-Medline search engine in order to find related studies published between 1985-2006 years with keywords “HIV,alcohol use dependence, substance use dependence, and psychiatric disorders”. In addition we used medical records about HIV-infected and carrier individuals’ sociodemographic data from TC Sağlık Bakanlığı Temel Sağlık Hizmetleri Genel Müdürlüğü Bulaşıcı ve Salgın Hastalıkların Kontrolü Daire Başkanlığı, Zührevi Hastalıklar Şubesi.Alcohol and/or substance abuse is a significant cause of comorbidity in HIV-seropositive patients, lowers the quality of life and causes problems with adherence to antiretroviral therapy. Unhealthy lifestyle, homelessness, unemployment, economic problems and stigmatization commonly observed in HIV(+) drug users, interferes with adherence to therapy. Central nervous system damage as a result of both drug use and HIV infections, increases individual and peripheral factors. HIV risk behaviors include unprotected sexual intercourse, having multiple partners, homosexual sex and sharing of injection equipment. There is a high risk of psychiatric and psychological disorders among HIV-infected individuals. Persons with AIDS have an increased risk of suicide, and assessment of such risk should be a standard practice in their care. Comorbidities such as mood disorders, psychotic disorders, anxiety disorders and personality disorders also interferes with adherence to therapy and aggravates risk taking behaviors. Substance abuse, comorbidity and risk taking behavior are more common among younger population. Early diagnosis and treatment could remarkably improve quality of life in this group of patients. Individuals with severe psychiatric problems commonly use drugs to facilitate relationships, decrease their anxiety and to increase social and vocational functioning. Adherence to therapy and decreasing risk taking behaviors can be achieved in substance dependent HIV patients with methadone and similar treatments.
Keywords: HIV; alcohol-substance dependence; psychiatric comorbidity